2023
DOI: 10.1055/a-2152-4762
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease and Cancer Risk in Patients with Venous Thromboembolism: What Does It Mean for Clinical Practice?

Stavros V. Konstantinides

Abstract: Non applicable for this type of article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…60 This study should alert physicians to be vigilant when focusing on kidney disease alone, as it could point to additional comorbidities and should reinforce existing guidelines recommending follow-up for patients 3 to 6 months postacute VTE potentially including cancer screening. 61 Other studies assessed safety of specific anticoagulation management in cancer patients. A retrospective review 62 indicated that both rivaroxaban and apixaban exhibited comparable effectiveness and safety in treating cancer-associated thrombosis over a 6-month period, suggesting the most suitable anticoagulant should be considered with regard to patient preferences, adherence, and individual patient-specific factors.…”
Section: At Risk!mentioning
confidence: 99%
“…60 This study should alert physicians to be vigilant when focusing on kidney disease alone, as it could point to additional comorbidities and should reinforce existing guidelines recommending follow-up for patients 3 to 6 months postacute VTE potentially including cancer screening. 61 Other studies assessed safety of specific anticoagulation management in cancer patients. A retrospective review 62 indicated that both rivaroxaban and apixaban exhibited comparable effectiveness and safety in treating cancer-associated thrombosis over a 6-month period, suggesting the most suitable anticoagulant should be considered with regard to patient preferences, adherence, and individual patient-specific factors.…”
Section: At Risk!mentioning
confidence: 99%